OF UKRAINIAN COMPONENT EXCURSION AND TOURIST ACTIVITY AS A HISTORICAL PHENOMENON AND EDUCATIONAL - Дудка, Т. Ю. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
This article analyzes the Ukrainian study component of excursion and tourism; as a powerful educational tool. By analyzing historiosophical essence of the educational phenomenon; outlined multi implement it in social and cultural space. Attention is focused on the cognitive potential of excursion and tourism; which helps enhance the full development of personality